Hukum Memakan Harta Anak Yatim Dan Ancamannya Perspetif Al-Quran - Samheri, Samheri (International Conference on Islamic Studies, 2020)
Kind of this research is literary research, and the metode of this research is qualitative reseach which collecting the data by analyze some refrences especially Tafsir, Fiqh, and another refrence as second data. Based on the data collected and analyezed the get a conclusion. The result of this research is the decision of Islamic law about the using the wealth of an orphan is fobiden and even comes with a threat to those who eat the wealth of an orphan threat for someone who user eat orphan’s property wrongfully and out of religion rule. Those who eat property of orphan actually swallowing fire and then they will go to the hell on the day of resurrection. Because of that the guardian of orphan suggested to not use property of orphan for personal needs. The final result of this reseach is the threat for someone who eat property of orphan, they are threatened by sa’ir hell, destruction in the world and hereafter.